Desempenho de sementes de milho tratadas com tiametoxam em função da dose e armazenamento - Nunes, João Carlos da Silva (2008)
The objective of this work was to verify the immediate and latent effects of the insecticide Thiamethoxam 350 FS, on physiological quality of maize hybrid seeds. Fifteen high quality hybrids of Monsanto company were utilized, studied through three variables: three rates of the insecticide Thiamethoxam as follow : 0, 0.7 and 1.05 mg of active ingredient/60,000 maize seeds; five storage periods (0, 3, 6, 9 e 12 months) e two storage types (15oC and without temperature control). The three parameters of evaluation were: germination, cold test and field emergence, all of them conducted in the Aprosmat Seed Testing Laboratory. The data were discussed based on statistical analysis about the isolated effect of the product Thiamethoxam and the ambient/storage interaction in which were obtained the following conclusions: 1 The maize seed can be treated with Thiamethoxam and remain stored for a period of one year under climatized environment; 2 An overrate of 50% above the recommendation does not affect the field emergence of the maize seeds; 3 Maize seed on a conventional environment without temperature and moisture control maintain their quality until six months of storage.; 4 High physiological quality of maize seeds can be stored for about 1 year on an environment with temperature below 20oC.